Analisis Yuridis Perlindungan Anak Dalam Kasus Perundungan (Bulliying) Disekolah Perspektif Restorative Justice (Studi SMP Negeri 1 Tanjung Morawa) - Ellena Saqia; Muhlizar Muhlizar; Dian Mandayani (Jurnal Ilmiah Penegakan Hukum, 2026)
This study examines the juridical aspects of child protection in school bullying cases from a restorative justice perspective, focusing on a case study at SMP Negeri 1 Tanjung Morawa. The research is motivated by the increasing incidence of bullying in schools, which has significant physical and psychological impacts on children, thus requiring effective legal protection. The objectives of this study are to analyze the regulation of bullying under Law Number 35 of 2014 on Child Protection, evaluate the implementation of child protection at the school level, and explore the integration of restorative justice principles in handling bullying cases. This research employs a normative juridical method with statutory and conceptual approaches, complemented by empirical data obtained through field interviews. The findings indicate that bullying is implicitly regulated under the prohibition of violence against children in the Child Protection Law. However, the implementation of legal protection at SMP Negeri 1 Tanjung Morawa still faces challenges, particularly in terms of understanding and handling mechanisms. The study further finds that the integration of restorative justice offers a viable alternative approach by emphasizing victim recovery, offender accountability, and the active involvement of schools and parents.